2016
DOI: 10.1101/lm.043141.116
|View full text |Cite
|
Sign up to set email alerts
|

Neural circuits via which single prolonged stress exposure leads to fear extinction retention deficits

Abstract: Single prolonged stress (SPS) has been used to examine mechanisms via which stress exposure leads to post-traumatic stress disorder symptoms. SPS induces fear extinction retention deficits, but neural circuits critical for mediating these deficits are unknown. To address this gap, we examined the effect of SPS on neural activity in brain regions critical for extinction retention (i.e., fear extinction circuit). These were the ventral hippocampus (vHipp), dorsal hippocampus (dHipp), basolateral amygdala (BLA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 83 publications
6
58
2
Order By: Relevance
“…Habituation and/or extinction resulting from repeated testing of anxiety, arousal, and fear reaction to SPS cues might attenuate PL and BLA activation without preventing the expression of fear which could be mediated by other nodes in the fear circuitry. This possibility is supported by the recent identification of novel neural substrates in the regulation of fear memory expression 55 . It is worth noting that while in our conditions, vulnerable rats were not able to activate the BLA and the PL in response to trauma reminders, emotional remodeling with oxytocin, which had no effect on control and resilient rats, not only reversed PTSD behavioral symptoms but also rendered the pattern of BLA and PL activation of vulnerable rats similar to the one of saline-injected resilient rats.…”
Section: Emotional Remodeling With Oxytocin and C-fos Expressionmentioning
confidence: 88%
“…Habituation and/or extinction resulting from repeated testing of anxiety, arousal, and fear reaction to SPS cues might attenuate PL and BLA activation without preventing the expression of fear which could be mediated by other nodes in the fear circuitry. This possibility is supported by the recent identification of novel neural substrates in the regulation of fear memory expression 55 . It is worth noting that while in our conditions, vulnerable rats were not able to activate the BLA and the PL in response to trauma reminders, emotional remodeling with oxytocin, which had no effect on control and resilient rats, not only reversed PTSD behavioral symptoms but also rendered the pattern of BLA and PL activation of vulnerable rats similar to the one of saline-injected resilient rats.…”
Section: Emotional Remodeling With Oxytocin and C-fos Expressionmentioning
confidence: 88%
“…49 reported that administration of SPS attenuated increases in ILC neural activity and failed to inhibit basolateral amygdala (BLA) neural activity in rats. 50 Third, the difference in cellular structure between naïve and SPS rats may play a role, since SPS has been reported to induce apoptosis in the ventral mPFC of rats. 51,52 Thus, in SPS rats, infusion of BDNF may be insufficient to reduce freezing behavior during extinction training or reexposure to context without any extinction training 48 hours after infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Second, differences in neuronal activity in the ILC between naïve and SPS rats could also be involved, as indicated in a study byKnox and associates, which reported that administration of SPS attenuated increases in ILC neural activity and failed to inhibit basolateral amygdala (BLA) neural activity in rats 50. In addition, they showed that BDNF infusion per se significantly decreased freezing behavior during the reexposure to context 48 hours after infusion without any extinction training.…”
mentioning
confidence: 99%
“…Many findings suggest that SPS produces behavioral and physiological symptoms that are similar to those observed in PTSD ( Liberzon et al, 1997 ; Kohda et al, 2007 ; Yamamoto et al, 2010 ; Knox et al, 2016 ). Examples of behavioral effects of SPS are illustrated in Figure 1 .…”
Section: Effects Of Sps On Behavior and The Brainmentioning
confidence: 93%
“…SPS rats demonstrate sleep abnormalities ( Vanderheyden et al, 2015 ) enhanced anxiety ( Han et al, 2014 ; Liu et al, 2016 ), arousal ( Khan and Liberzon, 2004 ), and fear learning ( Iwamoto et al, 2007 ; Keller et al, 2015b ) as well as impaired spatial and recognition memory, social interaction ( Kohda et al, 2007 ; Wen et al, 2016 ) and fear extinction ( Knox et al, 2012a ; Keller et al, 2015b ). Most changes are observed 7 days, but not 1 day, after exposure to the SPS procedure, suggesting that behavioral and cellular changes promoted by SPS are time-dependent ( Liberzon et al, 1999a ; Knox et al, 2016 ; Wu et al, 2016 ). Although it has been demonstrated that partial SPS does not generate extinction impairments ( Knox et al, 2012b ), the critical features of the SPS procedure for development of a PTSD-like phenotype remain unclear.…”
Section: Effects Of Sps On Behavior and The Brainmentioning
confidence: 97%